PERAN ORGANISASI KEROHANIAN ISLAM DALAM MEMBENTUK NILAI-NILAI AKHLAK KARIMAH BAGI SISWA SMAN 1 TAMANSARI (Institut Ummul Quro Al-Islami Bogor, 2025)
This study aims to determine the existence of an Islamic spiritual organization work program in an effort to shape the values of good morals in students of SMAN 1 Tamansari, The author uses qualitative research methods. Phenomenological approach in research to understand the phenomena experienced about research subjects such as perceptions, interests, behaviors, actions and motivations by means of descriptions in the form of language and words. Data collection through observation, interviews and documentation. The results that can show exemplary in the Islamic spiritual organization at SMAN 1 Tamansari is one of the Islamic spiritual organizations that can be called a da'wah institution at school in which there are things that have Islamic nuances that aim to facilitate students of SMAN 1 Tamansari in deepening religious knowledge. Internal and external obstacles are awareness of good morals that have not grown and have not become a priority, and a heterogeneous school environment in terms of morals is also dominated by those with poor morals, so that students are not so brave to appear with good morals, thus the Islamic spiritual organization has a management structure that aims to make the organization run properly as a da'wah institution in the school environment